Drafting international arbitration clauses - MacKinnon, Ari D. (2016)
This article offers an academic and practical overview for the drafting of international arbitration clauses, from an international Latin American approach and with special emphasis on the energy and construction industries.The authors begin by analyzing the elements of the existence of the arbitral clause and putting forward certain fundamental and general cautionary notes. Then they go on to analyze key elements to include in an arbitral clause, the elements which inclusion is recommended, the elements that might be convenient to include, and others that is best to leave out. The article ends with a conclusion regarding the mindset that parties should have when drafting arbitration clauses.